Household smoking and dental caries in schoolchildren: the Ryukyus Child Health Study - Sasaki Satoshi; Arakawa Masashi; Miyake Yoshihiro; Tanaka Keiko; Ohya Yukihiro (BMC, 2010)
Abstract Background Secondhand smoke exposure (SHSe) is perhaps one of the most important toxic exposures in childhood. However, epidemiological studies on the relation between SHSe and dental caries are limited and have yielded inconsistent results. The present cross-sectional study examined the potential association between SHSe at home and the prevalence of dental caries in children. Methods Subjects were 20,703 schoolchildren aged 6 to 15 years in Okinawa, Japan. Information on SHSe at home and potential confounding factors was obtained through questionnaires. Data on dental caries were obtained from school records. Children were classified as having decayed and/or filled teeth (DFT) if a dentist diagnosed these conditions. Additionally, we analyzed decayed teeth (DT) and filled teeth (FT) separately. Adjustment was made for sex, age, region of residence, toothbrushing frequency, use of fluoride, sugar intake, and paternal and maternal educational level. Results The prevalence of DFT was 82.0%. Compared with never smoking in the household, former and current household smoking were independently associated with an increased prevalence of DFT (adjusted prevalence ratios [95% confidence intervals] for former household smoking and current light and heavy household smoking were 1.03 [1.00-1.05], 1.04 [1.02-1.05], and 1.04 [1.03-1.06], respectively); when analyzed separately there was an increased prevalence of DT (adjusted prevalence ratios [95% confidence intervals] for former household smoking and current light and heavy household smoking were 1.06 [1.02-1.11], 1.10 [1.06-1.13], and 1.10 [1.07-1.14], respectively) but not FT. A statistically significant dose-response relationship between cumulative smoking in the household and the prevalence of DFT and DT (P for trend < 0.0001), but not FT, was observed. In an analysis of 2 subgroups, subjects who had at least 1 deciduous tooth and subjects who had at least 1 permanent tooth, household smoking exposure was associated with an increased prevalence of DFT and DT not only in those with deciduous but also those with permanent dentition. Conclusion Our findings suggested that household smoking might be associated with an increased prevalence of dental caries in children.